Предмет: Математика, автор: kamilaaaa213


a) 4(x + 3) = 5(x - 2);
6) -2(x - 5) + 3(x - 4) = 4x + 1;
B) 3(x - 1) = 2(x + 2);
r) 3(x - 5) - 2(x + 4) = -5x + 1.​

Ответы

Автор ответа: Iife20
4

Ответ:

Пошаговое объяснение:

а) 4(х+3)=5(х–2)

4х+12=5х–10

4х–5х= –10–12

–х= –22

х=22

б) –2(х–5)+3(х–4)=4х+1

–2х+10+3х–12=4х+1

х–4х=1+12–10

–3х=3

х=3÷(–3)

х= –1

в) 3(х–1)=2(х+2)

3х–3=2х+4

3х–2х=4+3

х=7

г) 3(х–5)–2(х+4)= –5х+1

3х–15–2х–8= –5х+1

х+5х=1+15+8

6х=24

х=24÷6

х=4

Похожие вопросы
Предмет: Английский язык, автор: Nikamironova9